Description about Requests in Saudi Pidgin Arabic - Hessah Al-Ageel (Modern Perspectives in Language, Literature and Education Vol. 8, 2021)
This study aims to investigate Saudi Pidgin Arabic (SPA) as one of the linguistic varieties that has emerged as a result of the interaction between Saudis and Asian workers. Linguistic and sociolinguistic analysis has been conducted for requestive expressions made by two generations of Saudi female speakers to female Asian workers in the cafeteria of a governmental institute in Riyadh, Saudi Arabia. The study reveals that the use of SPA is mostly limited to the most basic forms of verb and noun phrases found in Najdi Arabic (the type spoken in the Arabian Peninsula’s middle region), the SPA’s lexifier language. The impact of English on the younger generation is shown by the tendency of younger participants to employ English expressions. A sociolinguistic analysis also shows the impact of the social variables of power, status, social distance and the age of the requester.